APPLIED OF REASONED ACTION THEORY (TRA) YANG BERDAMPAK PADA INTENTION TO PURCHASE HERBAL COSMETICS - Ivon Jalil; Yayuk Eko Wahyuningsih; Leli Putri Ansari (universitas teuku umar, 2019)
This research discussed about the effect of beauty advisor’s ability and trust belief on cosmetics store on consumer’s intention to purchase herbal cosmetics which used the Theory of Reasoned Action that involving mediation of attitude and subjective norm. 200 respondents who invited the store. Results show that beauty advisor’s ability and trust belief on cosmetics store affect consumer’s intention to purchase herbal cosmetics through mediation of attitude and subjective norm. Herbal Cosmetics perceive more better and safety who consumtion with excellent service beauty advisor made satisfaction consumer’s effect to intention to purchase at the store.Key words: cosmetics; purchase intention; beauty advisor's ability; Theory of Reasoned Action; trust belief.